Development and Validation of School Adolescents Mental health Assessment Tool (SAMAT) - Radhakrishnan Govindan; G Balamurugan; T M Deekshitha; R Tejashwini; Prasanthi Nattala; Rajani Parthasarathi; K. M. Rajendra; Channaveerachari N. Kumar (Journal of Family Medicine and Primary Care)
Background: Teachers are the first line of contact for children for any concerns. They are crucial in identifying all health issues, including mental health issues. However, the teachers may not have adequate knowledge of the concerns with children’s and adolescents’ mental health in schools. School enrollments have grown in India at every level, from primary to higher secondary, and school dropout rates have steadily declined in recent years. In parallel, from the 2013 fiscal year to 2022, the pupil–teacher ratio consistently improved at all levels. Hence, school teachers play a vital role in students’ mental health. The study aims to create a tool teachers may use to screen, identify, refer, and follow-up with adolescents’ mental health enrolled in classes. Materials and Methods: The present study was carried out in four phases: literature search, focused group discussions with teachers, development and validation of SAMAT. The number of teachers is 110. Results: The School Adolescents Mental Health Assessment Tool has ten items derived from the thematic analysis of the literature review, focused group discussions with teachers during the training session about general mental health awareness and adolescents’ mental health concerns and inputs from 5 mental health professionals. The instrument displayed a high content validity index (S-CVI = 1) and high item-level content validity index (I-CVI: 1). Reliability was calculated using the Cronbach alpha reliability method. Conclusion: SAMAT has high I-CVI and S-CVI and good Cronbach alpha reliability. This tool will support educators in formally evaluating pupils by assisting with the screening, identification, initial mental health support, referral, and follow-up of adolescents with mental health concerns.